La mediación lingüística en la enseñanza de lenguas - Arriba García, Clara De; Cantero Serena, Francisco José (Didáctica. Lengua y Literatura, 2004)
In this article we explain the concept of linguistic mediation and its implications in language teaching, in a multilingual society. We establish the mediation types and the linguistic skills to work in the classroom. Finally, we suggest the place of mediation in the communicative competence and its relationship with the sub-competences.